DECISION THEORY WITHOUT FINITE STANDARD EXPECTED VALUE. (13th August 2015) - Lauwers, Luc; Vallentyne, Peter
Abstract: We address the question, in decision theory, of how the value of risky options (gambles) should be assessed when they have no finite standard expected value, that is, where the sum of the probability-weighted payoffs is infinite or not well defined. We endorse, combine and extend (1) the proposal of Easwaran (2008 ) to evaluate options on the basis of their weak expected value, and (2) the proposal of Colyvan (2008 ) to rank options on the basis of their relative expected value.